Monitoring Anurans Diversity along Code River, Province of Daerah Istimewa Yogyakarta, Indonesia - Yudha, Donan Satria; Akmal, Wulan Rahmani; Eprilurahman, Rury (Biogenesis: Jurnal Ilmiah Biologi, 2019)
The research about frogs and toads diversity in the Code River, Province of Daerah Istimewa Yogyakarta (DIY) had been done in 2012 (Yudha et al., 2013). Now, after five years passed, we conduct monitoring activities for updating its diversity and distribution. After five years, we consider that there are many changes along the river that influenced habitat condition for frogs and toads which live along and near the river. Some of the changes are unused land became human settlement or paddy fields and wasteland. The purpose of this research is to monitor the diversity of frogs and toads after five years along Code River. The method used was acoustic and visual encounter survey (VES). We have done total of 10 days of sampling. Each day we did two times sampling, during the day and night. Results show that the species number of frogs and toads found in 2012 were slightly higher compare to 2017. The frogs and toads on upstream part were diverse in 2017 compare to 2012 due to natural restoration of riparian vegetation occur on upstream. The frogs and toads on midstream part were less diverse in 2017 compared to 2012 due to increasing human activities near the river and less riparian vegetation. The frogs and toads on downstream part were also less diverse in 2017 compared to 2012 due to increasing human activities near the river and more household waste stuck on riparian vegetation. There was variation of anurans diversity after five years due to changing on physical condition of the river and human activities near the river.